Impact of Sevoflurane Versus Propofol Anesthesia on Post-Operative Cognitive Dysfunction in Elderly Cancer Patients: A Double-Blinded Randomized Controlled Trial - Guo, Liang (Med Sci Monit, 2020)
BACKGROUND: Research on the clinical outcomes of surgical patients anaesthetized with sevoflurane and the association of sevoflurane with post-operative cognitive dysfunction (POCD) is scarce. We evaluated whether sevoflurane-based anesthesia increased the incidence of POCD and worsened prognosis compared to propofol-based anesthesia in elderly cancer patients. MATERIAL/METHODS: This single-center, prospective, double-blind randomized controlled trial included 234 patients aged 65 to 86 years undergoing tumor resection who received sevoflurane-based (Group S) or propofol-based (Group P) anesthesia during surgery. A series of neuropsychological tests was performed to evaluate cognitive function before surgery and at 7 days and 3 months post-operation, and the results were compared to those of healthy controls. RESULTS: At 7 days post-operation there were no significant differences in the incidence of POCD between patients who received sevoflurane-based or propofol-based anesthesia during surgery: Group S was at 29.1% (32 out of 110 patients) versus Group P at 27.3% (30 out of 110), P=0.764. At 3 months, Group S was at 11.3% (12 out of 106 patients) versus Group P at 9.2% (10 out of 109), P=0.604. During the first 2 days post-operation, the QoR-40 global score was significantly lower in Group S compared to Group P [POD 1: P=0.004; POD 2: P=0.001]. There were no significant differences in in-hospital post-operative complications, post-operative length of hospital stay, all-cause mortality at 30 days, and 3 months post-operation, or post-operative quality of life at 3 months between patients in Group S and Group P. CONCLUSIONS: Sevoflurane-based anesthesia did not increase the incidence of POCD compared to propofol-based anesthesia at 7 days or 3 months post-operation or impact short-term post-operative prognosis.